SKRINING PESTISIDA, PARASIT PADA BUAH DAN SAYUR PADA IBU-IBU PKK GUJI BARU KEPA DURI, KEBUN JERUK, JAKARTA BARAT - Monica Puspa Sari; Susilowati, Rina Priastini (Servirisma, 2023)
Fruits and vegetables are foods that are rich in nutrients such as vitamin and minerals, which are good for the body to consume to improve health. However, what should be a concern for the consumption of fruits and vegetables is the presence of contaminants such as pesticide residues and the presence of parasites in fruits and vegetables. The purpose of this community service is to provide counseling and demonstrations on how to screen vegetables and fruits from pesticides and parasites to PKK Guji Baru women with a community based research approach. A total of 49 mothers participated in this community service activity. A total of 16 (55,17%) counseling participants were aged between 41-50 years, while based on education, the average education level was high school completion as many as 20 people (40,81%) and based on occupation as many as 42 (85,71%) participants were housewife. Based on the level of knowledge of the 7 questions, the average level of knowledge of PKK mothers is 79% while the level of behavior is 68,18%. It is hoped that there will be change in the behavior of PKK mothers in processing vegetables and fruits properly so as to produce healthy food for the family.